2023
DOI: 10.1093/infdis/jiad197
|View full text |Cite
|
Sign up to set email alerts
|

Seroprofiling of Antibodies Against Endemic Human Coronaviruses and Severe Acute Respiratory Syndrome Coronavirus 2 in a Human Immunodeficiency Virus Cohort in Lesotho: Correlates of Antibody Response and Seropositivity

Abstract: Background Serological data on endemic human coronaviruses (HCoVs) and SARS-CoV-2 in southern Africa are scarce. Here, we report on i) endemic HCoV seasonality, ii) SARS-CoV-2 seroprevalence, and iii) predictive factors for SARS-CoV-2 seropositivity and strength of SARS-CoV-2 and HCoV serological response during a 17-month period at the start of the COVID-19 pandemic among adults living with HIV. Methods Plasma samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Previous work by us and others strongly suggests a beneficial effect of HCoV immunity in reducing SARS-CoV-2 acquisition and disease severity ( 21 , 22 , 25 , 27 , 28 ), while other studies found no or little effect ( 33 , 34 ). Here, we considered that the discrepancy in results may in part be due to a different relative timing of SARS-CoV-2 and HCoV infections in individual cohorts, as HCoV infections have a pronounced seasonality with the four HCoV strains fluctuating annually and geographically ( 29 , 36 , 37 ). We concluded that a pairwise analysis of pre-infection samples and early post-infection SARS-CoV-2 seropositive samples in a population from the same geographic region during the same time period is needed to provide a controlled framework for studying the impact of HCoV immunity on SARS-CoV-2 antibody responses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work by us and others strongly suggests a beneficial effect of HCoV immunity in reducing SARS-CoV-2 acquisition and disease severity ( 21 , 22 , 25 , 27 , 28 ), while other studies found no or little effect ( 33 , 34 ). Here, we considered that the discrepancy in results may in part be due to a different relative timing of SARS-CoV-2 and HCoV infections in individual cohorts, as HCoV infections have a pronounced seasonality with the four HCoV strains fluctuating annually and geographically ( 29 , 36 , 37 ). We concluded that a pairwise analysis of pre-infection samples and early post-infection SARS-CoV-2 seropositive samples in a population from the same geographic region during the same time period is needed to provide a controlled framework for studying the impact of HCoV immunity on SARS-CoV-2 antibody responses.…”
Section: Resultsmentioning
confidence: 99%
“…Although SARS-CoV-2 is not closely related to endemic human coronaviruses (HCoVs), sequence homologies exist and give rise to both cross-reactive antibody and T cell responses ( 18 26 ). Indeed, research from others and us has highlighted that pre-existing immunity to HCoVs may limit disease severity either directly ( 27 ) or by supporting the development of SARS-CoV-2-specific humoral ( 22 , 27 29 ) and cellular ( 21 ) responses. Cross-reactive HCoV T cell responses ( 21 , 30 ) and cross-reactive HCoV antibodies ( 31 , 32 ) have been postulated to underlie the milder presentation of COVID-19 in children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations